Temperamental Prerequisites of Personality Self-Realization - S I Kudinov; S R Aybazova; K V Arkhipochkina (Peoples' Friendship University of Russia (RUDN University), 2015)
The article discusses the problem of individual and typological conditionality of personality self-realization. The results of an empirical research are submitted, the typological features of temperament properties with the variables of self-realization in teachers are compared.